Bozena Nemcova's life from three points of view (Milos Urban, Frantisek Novotny, Lenka Lagronova) - Pajak, Aleksandra (Bohemica Olomucensia, 2018)
The paper employs Aby Warburg's concept of Nachleben to analyse Bozena Nemcova's figure. It concentrates on her images created after 1989 which constitute a sign of breaking the cultural taboo. In Urban's action novel, she is demythologized in the intermezzi that are ostensibly unrelated to the actual plot. Novotny's figuratively and literally ``undresses'' the writer, whereas Lagronova demonstrates the woman's tragedy as a victim of other people's desires.
Keywords: deheroisation; ``second life''; cultural taboo; Bozena Nemcova; Milos Urban; Frantisek Novotny; Lenka Lagronova